Genome-wide association and high-resolution phenotyping link Oryza sativa panicle traits to numerous trait-specific QTL clusters - Samuel Crowell (Nature Portfolio, 2016)
Panicle architecture is an important determinant of crop yield and a target of selection by plant breeders. Here, Crowell et al.combine image-based phenotyping with high-density array-based genotyping to perform a genome-wide association study revealing a number of candidate genes linked to panicle variation in rice.